The cellular mechanisms associated with the anesthetic and neuroprotective properties of xenon: a systematic review of the preclinical literature - McGuigan, Steven; Marie, Daniel J.; O'Bryan, Liam J.; Flores, Francisco J.; Evered, Lisbeth; Silbert, Brendan; Scott, David A. (Frontiers in Neuroscience, 2023)
Xenon exhibits significant neuroprotection against a wide range of neurological insults in animal models. These include injuries associated with anesthesia and surgery, traumatic brain injury and hypoxic-ischemic injury. Despite this, clinical evidence that xenon improves outcomes in human studies of neurological injury remains elusive. Failure to translate therapeutics from bench to bedside can occur due to flawed methodology in preclinical studies, leading to bias and unreliable conclusions. Previous reviews of the preclinical literature examining xenon method of action have been narrative in nature. The aim of this review is to provide a comprehensive summary of the cellular interactions responsible for two phenomena associated with xenon administration: anesthesia and neuroprotection. It does so by applying a systematic review methodology to the preclinical literature. The review identified 69 articles describing 638 individual experiments in which a hypothesis was tested regarding the interaction of xenon with cellular targets including membrane bound proteins, intracellular signaling cascades and transcription factors. The review identified both common and subtype specific interactions between xenon and ionotropic glutamate receptors. The review also identified interactions with receptors for inhibitory neurotransmitters, other ligand gated channels and several non-ligand gated membrane bound proteins. The review identified several intracellular signaling pathways and gene transcription factors that are influenced by xenon administration and might be responsible for neuroprotection observed in animal models. The unique nature of xenon NMDA receptor antagonism, and its other cellular targets, are discussed with specific comparisons to ketamine, nitrous oxide and other anesthetic agents. The cellular targets responsible for xenon neuroprotection are also discussed in the context of other anesthetics that display neuroprotective properties. It is hoped that identification of the underlying cellular targets of xenon might aid the development of potential therapeutics for neurological injury and improve the clinical utilization of xenon.